Analisis Biaya Langsung Medis Terapi Seftriakson Dibandingkan Dengan Levofloksasin Pada Pasien Pneumonia Komunitas di Rumah Sakit Pemerintah X NTB - Cyntiya Rahmawati; Baiq Leny Nopitasari (Fakultas Farmasi Universitas Setia Budi, 2021)
Pneumonia is a respiratory tract infection with the highest number of cases in Government Hospital X in NTB in 2018. The worst impact of pneumonia are death and high cost of health services risk. So management of costs is needed for effectively and efficiently. The therapeutic choice for community acquired pneumonia (CAP) used in X Hospital is ceftriaxone and levofloxacin which have a high price difference. This study aims to calculate the average direct medical costs in hospitalized CAP patients who use ceftriaxone and levofloxacin therapy at Government Hospital X in NTB in 2018. This research type is quantitative analysis using secondary data that compares the average direct medical costs of two alternative treatments for CAP with the BPJS Kesehatan perspective. The cost component are cost of medicine, care, doctor, emergency room, accommodation, and laboratory. The number of samples was 65 patients. The results showed: (1) The average direct medical costs using ceftriaxone was Rp.3.034.965, while levofloxacin was Rp.1.594.053; (2) There is significant difference in the average direct medical cost of Rp.1.440.912 perpatient; (3) Levofloxacin provide the lowest rupiah than ceftriaxone in community acquired pneumonia patients.